800 MPa Class HSLA Steel Block Part Fabricated by WAAM for Building Applications: Tensile Properties at Ambient and Elevated (600°C) Temperature. (4th February 2022) - Fang, Qian; Zhao, Lin; Chen, Cui-xin; Cao, Yang; Song, Liang; Peng, Yun; Yin, Fu-xing
Abstract : An 800 MPa class high strength low-alloy (HSLA) steel block part was deposited on substrate with similar composition by gas metal arc welding (GMAW)-based wire arc additive manufacturing (WAAM). The base plate could be removed after deposition or retained as part of the additive manufacturing (AM) part, forming the hybrid additive manufacturing (HAM) part. Tensile tests of the AM part and the HAM part were performed at ambient temperature (AT) and elevated temperature (ET, 600°C held for 4 h) for potential applications in high-rise buildings. Microstructure observations and low temperature impact tests were also conducted. Results show that microstructure of the deposit mainly consists of lower bainite and granular bainite. AT yield strength (YS) of the deposit along the deposition, transverse, and vertical directions is ∼770 MPa. ET YS of the deposit along the lateral and building directions could reach 373 MPa, 48.4% of the AT YS. Fracture elongation along all directions could exceed 18.0% for both AT and ET. Low temperature (−50°C) impact absorbed energy of the deposit could exceed 84 J along all directions. Mechanical properties of the HAM part are similar or superior to those of the AM part along the vertical direction, except the AT fracture elongation, which is one-fifth lower. Good strength-ductility-toughness balance of the made part verified the feasibility of using WAAM to manufacture 800 MPa HSLA steel block parts that have potential applications in high-rise buildings, especially considering ET YS of the part might be improved by alloying redesign to meet the performance requirements of building steel.